Improving the microbiological diagnosis of tuberculous meningitis: A prospective, international, multicentre comparison of conventional and modified Ziehl–Neelsen stain, GeneXpert, and culture of cerebrospinal fluid. Issue 6 (December 2018) - Heemskerk, A. Dorothee; Donovan, Joseph; Thu, Do Dang Anh; Marais, Suzaan; Chaidir, Lidya; Dung, Vu Thi Mong; Centner, Chad M.; Ha, Vu Thi Ngoc; Annisa, Jessi; Dian, Sofiati; Bovijn, Louise; Mai, Nguyen Thi Hoang; et al.
Highlights: Modified ZN staining of CSF with a cytospin step was not superior to conventional ZN staining for the diagnosis of TBM. Modified ZN staining of CSF without a cytospin step was inferior to conventional ZN staining for the diagnosis of TBM. Higher CSF volume and lactate, and lower blood glucose ratio were independently associated with microbiological confirmation of TBM. Summary: Objectives: Tuberculous meningitis (TBM) is the severest form of tuberculosis, but current diagnostic tests are insensitive. Recent reports suggest simple modifications to conventional cerebrospinal fluid (CSF) Ziehl–Neelsen (ZN) staining may greatly improve sensitivity. We sought to define the performance of modified and conventional ZN stain for TBM diagnosis. Methods: In hospitals in Vietnam, South Africa and Indonesia we conducted a prospective study of modified ZN with or without cytospin, conventional ZN smear, GeneXpert, and culture on CSF in adults with suspected TBM. Results: A total of 618 individuals were enrolled across 3 sites. Compared with the TBM clinical diagnostic gold standard for research (definite probable or possible TBM), sensitivity of conventional ZN and modified ZN with cytospin were 33.9% and 34.5% respectively ( p  = 1.0 for the difference between tests), compared with culture 31.8% and Xpert 25.1%. Using culture as a reference, sensitivities of conventional ZN, modified ZN with cytospin, and Xpert were 66.4%, 67.5%, and 72.3%, respectively. Higher CSF volume and lactate, and lower CSF:blood glucose ratio were independently associated with microbiologically confirmed TBM. Conclusions: Modified ZN stain does not improve diagnosis of TBM. Currently available tests are insensitive, but testing large CSF volumes improves performance. New diagnostic tests for TBM are urgently required.